THE DEVELOPMENT OF CONTEXTUAL LEARNING BASED TEXTBOOK TO IMPROVE STUDENTSâ CRITICAL AND CREATIVE THINKING ABILITY OF ISLAMIC EDUCTION SUBJECT AT MAN SURABAYA - Rahmat, Arofah (Studia Religia, 2018)
AbstractThis study aimed to identify: (1) the validity of the developed contextuallearning based textbook (2) practicality of the developed contextual learningbased textbook (3) effectiveness of the developed contextual learning basedtextbook to improve studentsâ critical and creative thinking ability. This studyused developement research design by adopting ADDIE model (Analysis,Design, Development, Implementation, and Evaluation). This study consistedof three stages: introduction, developement, and test of effetiveness. Thevalidity result of textbook from 36 expertâs assessment items showed that 22items were very suitable and 14 items were suitable. The textbook practicalitywas seen from checklist points achievement for contextual learning basedtextbook. The result of gain score analysis of students âcritical thinking abilitywas 0.769 or categorized as high, meaning that the use of contextual learningbased textbook was effective to improve studentsâ critical thinking ability. Theresult of gain score analysis of students âcreative thinking ability was 0.775 orcategorized as high, meaning that the use of contextual learning based textbookwas effective to improve studentsâ creative thinking ability